Invite Only Dinner with Bernard Witkin at Basque Hotel - Watkins, Howard::::::::: (1986)
Bernard Witkin talking; head table: Judges James V. Paige and Frank Creede, Jr., Witkin, Judge Robert Coyle and James Gregory